2001
DOI: 10.1080/10862960109548113
|View full text |Cite
|
Sign up to set email alerts
|

“I Can't Wait to See Carlos!”: Preservice Teachers, Situated Learning, and Personal Relationships with Students

Abstract: In this study, we examined the reflections of 71 preservice teachers as they tutored literacy in a predominantly Hispanic American, low-income school. The carefully structured, intensively supervised practicum for each preservice teacher combined situated learning with guided critical reflection in the context of a relationship with one elementary student. Working within the framework of caring and its influence on socially mediated learning, we also explored the nature of personal relationships. Judging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…Our study supported the findings of previous researchers (Worthy & Patterson, 2001) that the development of caring relationships in a tutor-tutee setting provided a rich learning environment in which to develop PTCs understanding of the complexities of teaching and learning. The faculty's support of the development of these relationships allowed us to focus on several goals: 1) helping PTCs relate to ELLs as individuals with personal histories rather than as a monolithic group; 2) helping PTCs learn to discern and develop different teaching roles; and 3) using the development of the tutoring relationship to help the PTCs recognize the need for additional professional development to help them learn to teach specialized content such as math, science, and reading.…”
Section: Limitations and Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Our study supported the findings of previous researchers (Worthy & Patterson, 2001) that the development of caring relationships in a tutor-tutee setting provided a rich learning environment in which to develop PTCs understanding of the complexities of teaching and learning. The faculty's support of the development of these relationships allowed us to focus on several goals: 1) helping PTCs relate to ELLs as individuals with personal histories rather than as a monolithic group; 2) helping PTCs learn to discern and develop different teaching roles; and 3) using the development of the tutoring relationship to help the PTCs recognize the need for additional professional development to help them learn to teach specialized content such as math, science, and reading.…”
Section: Limitations and Implicationssupporting
confidence: 90%
“…The importance of meaningful and collaborative contexts for reflective practice and establishing caring relationships between tutors and tutees was emphasized in a study by Worthy and Patterson (2001). Although this study was focused on the development of tutors' understanding of literacy and literacy teaching, the researchers also found preliminary evidence that the tutors' experiences led to changes in perceptions and biases related to tutees' ethnicity, social class, and language background.…”
Section: Teacher Perceptions Of English Language Learnersmentioning
confidence: 97%
“…Our goal in the IMAP project was to take advantage of prospective teachers' interest in children. Others have found that the personal relationships that emerge from individual tutoring sessions have positively affected prospective teachers' learning in the domain of reading instruction (Worthy & Patterson, 2001). We hoped that while they worked with children in the domain of doing mathematics, the prospective teachers' interest in their students would motivate them to expand their view of teaching and of mathematics when they encountered the limitations of an exclusive 'teaching as explaining' approach.…”
Section: Prospective Teachers Beliefs About the Nature Of Teachingmentioning
confidence: 99%
“…Finally, preservice teacher participants were able to emphasize and strengthen what was previously learned in the classroom, create questions that could define future learning, experience nonacademic issues they may encounter in the classroom, and view the fact that lessons need to be adjusted to the needs of individual children. Worthy and Patterson (2001) also used e-mail to examine the written reflections of 71 pre-service teachers who were enrolled in a reading education course and tutored elementary school children during a 1-year teacher preparation program. These researchers found that as time passed, the participants showed a shift from concerns about teaching to meet the individual needs of their students and modifying behavioral issues.…”
Section: Lack Of Change or Negative Change In Pre-service Teacher Effmentioning
confidence: 99%